Проблеми безпеки та захисту інформації в хмарних сховищах - Леонова, А. О. (ХНУРЕ, 2024)
Instead of storing files on your company's hard drive or local storage device, you can use cloud storage, which allows you to store them in a remote database. Cloud storage is becoming increasingly popular among people who need more storage space and for businesses looking for an efficient off-premises data backup solution. Due to the growing popularity and use of cloud storage, cloud security has become a major concern to protect data integrity, prevent hacking attempts, and prevent file or personal data theft.
Keywords: захисту інформації в хмарних сховищах; хмарне сховище